2009
DOI: 10.3837/tiis.2009.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent Lighting Control using Wireless Sensor Networks for Media Production

Abstract: We present the design and implementation of a unique sensing and actuation application-the Illuminator: a sensor network-based intelligent light control system for entertainment and media production. Unlike most sensor network applications, which focus on sensing alone, a distinctive aspect of the Illuminator is that it closes the loop from light sensing to lighting control. We describe the Illuminator's design requirements, system architecture, algorithms, implementation and experimental results. The system u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Besides that, human motion tracking is a promising technique for remote nursing and rehabilitation, in which the patient at home might be nursed or helped by a remote doctor via the Internet [1]. Similar applications can be found in the intelligent media [2], movie making [7] and sports training [6]. Additionally, motion tracking can be used for robot control [9] and new weapon training [17].…”
Section: Introductionmentioning
confidence: 99%
“…Besides that, human motion tracking is a promising technique for remote nursing and rehabilitation, in which the patient at home might be nursed or helped by a remote doctor via the Internet [1]. Similar applications can be found in the intelligent media [2], movie making [7] and sports training [6]. Additionally, motion tracking can be used for robot control [9] and new weapon training [17].…”
Section: Introductionmentioning
confidence: 99%
“…Like Internet, the IoT also has the potential to change the world and the life style of people [4]. The research on the IoT is still at the basic stage.…”
Section: Introductionmentioning
confidence: 99%
“…Many have suggested that the utilization of building energy management systems potentially leads to 25-40% energy savings from smart control of heating, ventilation, air conditioning (HVAC), and lighting [2][3][4]. Applications of WSN for building energy management system have been addressed in [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%